Potentiometric Studies on Binary and Ternary Complexes of Transition Metal Ions with Some Pharmaceutical Compounds - Patil, A.B.; Mhaske, T.H. (Asian Journal of Chemistry, 2010)
To explore the binary and ternary complexation tendencies of Mn(lI), Co(lI), Ni(lI), Cu(lI) and Zn(lI) were studied by the pH-metric technique at the ionic strength 0.1 M (KNO3) and the temperature 29 ± 0.5°C in aqueous medium. The metal-ligand stability constants of binary complexes were evaluated using Irving-Rossotti titration technique. The metal-ligand stability constants were evaluated using nitrolotriacetic acid (NTA) and iminodiacetic acid (IMDA) as primary ligands and the drugs levodopa (LDP) and methyldopa (MDP) as secondary ligands at the same conditions by the modified form of Irving-Rossotti technique.